2006
DOI: 10.1002/mds.20877
|View full text |Cite
|
Sign up to set email alerts
|

Regional brain volumes distinguish PSP, MSA‐P, and PD: MRI‐based clinico‐radiological correlations

Abstract: Progressive supranuclear palsy (PSP) and multiple system atrophy (MSA) are neurodegenerative disorders, each with a prevalence of around 5 per 100,000. Regional brain atrophy patterns differ in the two disorders, however, and magnetic resonance imaging is sometimes helpful in distinguishing them in the later stages. We measured whole brain and regional volumes, including cerebellum, pons, midbrain, superior cerebellar peduncle (SCP), and ventricular volumes as well as frontal and posterior-inferior cerebral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
96
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 40 publications
9
96
0
2
Order By: Relevance
“…Nonspecific brain atrophy in regions with atrophic changes associated with/without dementia has been reported in several previous studies, with an absence of consistent results. [6][7][8][9][10][11][30][31][32] The cause of the variability among these findings remains uncertain. However, the results of our study showed that the loss of volume of brain structures in PD varies according to region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonspecific brain atrophy in regions with atrophic changes associated with/without dementia has been reported in several previous studies, with an absence of consistent results. [6][7][8][9][10][11][30][31][32] The cause of the variability among these findings remains uncertain. However, the results of our study showed that the loss of volume of brain structures in PD varies according to region.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Studies of variation of regional brain volume, such as striatal volume, have yielded inconsistent results. [9][10][11][12] In patients with PD, the natural balance of the basal ganglia circuitry is functionally lost because of dopamine depletion. Sequential imbalances lead to overexcitation of inhibitory GABAergic neurons in the globus pallidus interna/subthalamic nucleus via direct and indirect pathways, which results in profound inhibition of the thalamus.…”
mentioning
confidence: 99%
“…MRI can play a valuable role in discriminating atypical parkinsonian syndromes, such as multiple-system atrophy and progressive supranuclear palsy, from typical PD. Atrophy of the lentiform nucleus is a feature of these atypical disorders, but volumetric MRI has not proved sensitive enough to be of diagnostic value (20,21). In contrast, diffusion-weighted and diffusion tensor MRI is highly sensitive to changes in striatal structure and potentially useful for discriminating atypical from typical parkinsonian disorders.…”
Section: Transcranial Sonographymentioning
confidence: 99%
“…Additionally, there is strong potential that these techniques could be translated to clinical field strengths, as indicated by Meadowcroft et al (18), which underscores the potential for correlative MR imaging-based pathologic evaluations and the prospect for translation to diagnostic imaging in the differential diagnoses of parkinsonian disorders. Interestingly, previous in vivo MR imaging studies have focused on morphometric analyses to quantify atrophy in the midbrain, pons, and cerebellar peduncles and to differentiate PSP from other movement disorders (7,19). Though these morphometric techniques have good sensitivity, the relaxation-based approach utilized here may provide novel indices that will improve diagnostic imaging of parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…There has been great progress in the clinical assessment of neurodegenerative disorders, including PSP, with the use of magnetic resonance (MR) imaging (1,7). However, the definitive diagnosis of these various degenerative conditions still must be confirmed with postmortem examination.…”
Section: Methodsmentioning
confidence: 99%